The parasitoid complex associated with the olive fly, Bactrocera oleae, in Southern Portugal (Algarve) - Gonçalves, Maria (2016)
The olive fly, Bactrocera oleae (Gmelin), is the most destructive pest of the olive trees in the Mediterranean Basin. Since 2004 several studies have been carried out in order to identify the beneficial insect species of the Hymenoptera order that usually inhabiting the olive ecosystem in Algarve. For that purpose samples of infested olive fruits were collected during the autumn season from several olive trees at Loulé and S. Brás de Alportel regions. The collected fruits were placed in laboratory conditions (temp.: 23 ± 2 °C; 60 ± 5% relative humidity and 12 light: 12 dark photoperiod cycle) until larvae completed their development and left the fruit to pupate. After that they were collected and placed into a small glass tubes with a honey drop until the emergence of the adults in the same laboratory conditions. Adults of the parasitoids were characterized and identified. The obtained results showed that the most abundant Hymenoptera species of the parasitoid complex associated with the olive fly in Algarve are Psytallia (Opius) concolor (Hym.: Braconidae), Pnigalio mediterraneus (Hym.: Eulophidae) and Cytoptyx latipes (Hym.: Pteromalidae).